Turkey and the European Union : domestic politics, economic integration, and international dynamics - Çarkoğlu, Ali, 1963-; Rubin, Barry M. (Frank Cass, 2003)
"Turkey's relations with an enlarging European Union have long been hit by recurrent crises and problems of adjustment within internal domestic politics as well as from an external, international relations perspective. This book aims to provide an up-to-date review of relevant issues from both perspectives. Analyses focus on the significance of EU adjustment processes for Turkish domestic politics and public opinion. From the perspective of economic dynamics, analyses focus on the impact of a customs union with the EU and the issues surrounding the impending economic policy adjustments. Justice and home affairs issues and human rights practices are two areas where specific policy adjustments are needed in order to conform to the Copenhagen criteria. These adjustments are seen as touching on sensitive domestic politics issues and the analyses herein evaluate the recent developments in these policy areas. In light of these discussions, the book offers an overall evaluation of Turkey's bid for full membership in the EU."--Jacket